The Effect of Curriculum Implementation on the Performance of SDIT Albanna Denpasar Teachers - Rizka Mauliddina; Imam Muhayat (Al-Hayat: Journal of Islamic Education, 2020)
Curriculum implementation and teacher performance are one of the important factors in educational success. Discussing of the curriculum as a program of learning under the responsibility of the school. In reality, in SDIT Albanna Denpasar have variations in the ability of educators in the level of curriculum attainment, curriculum making is made by all school principals and all curriculum department representatives. Which is likely to affect teacher performance. The objectives of this research are to determine: 1) The effect of curriculum implementation on teacher performance at SDIT Albanna Denpasar in the2020 Academic Year 2) The contribution of curriculum implementation contribute to the teacher performance at SDIT Albanna Denpasar in the 2020 Academic Year. This research is quantitative correlational research. Data collection techniques used in this study were to use questionnaires, observastion, and documentation. The results showed that: 1) there was significant effect of curriculum implementation to the performance of teachers in SDIT Albanna Denpasar. This’s indicated by the curriculum implementation variable having a positive,And it’s also known that F linearity Fcount>Ftable was 0.956 < 4.15, This means Ho was accepted and Ha was rejected, so meaning regretion linier. 2) the curriculum implementation variable (X) has a simultaneous contribution of 16,5 % to the teacher performance variable (Y) the remaining 83,5 % is influenced by other factors not examined in this research.